Women's Representation and Accessibility in Indonesian Politics: A Study of Jakarta Regional People's Representative Council - Kadriyah, S. Maryamah (UI Scholars Hub, 2023)
This research delves into the challenges and dynamics of women’s political participation in Jakarta, Indonesia. Despite legal frameworks advocating gender equality, like the 30% representation quota, women members of Parliament (MPs) in Jakarta’s politics face significant hurdles, predominantly rooted in a deeply entrenched patriarchal culture. Utilising a qualitative methodology, the study involved comprehensive interviews with female members of Jakarta’s DPRD. The findings reveal a complex interplay of educational background, political motivations, party dynamics, and societal perceptions influencing women’s political careers. The underrepresentation of women in parliament hinders effective gender-centric policy formulation, underscoring the need for enhanced descriptive and substantive representation. This study contributes to a deeper understanding of the barriers women face in politics, emphasising the need for targeted strategies to dismantle these barriers and promote gender equality in political representation in Jakarta and in wider scope Indonesian politics.